Numerical and experimental modeling of a new anti-tension equipment for high-rise isolation buildings. (15th January 2019) - Shen, Chao-yong; Chen, Yang-yang; Huang, Xiang-yun; Tan, Pin; Ma, Yu-hong
Highlights: A new type of anti-tension equipment used in isolation building is proposed. The equipment with double column and steel brace may be more convenient and practicable after analyzed by FEA in detail. A scale model was tested, test results have good agreement with that of FEA. Abstract: When the height-width ratio of high-rise isolation buildings is excessively large, elastomeric isolators may suffer from tension in severe earthquakes. Because of the tension limits of isolators, an anti-tension equipment must be added to such buildings for safety. In this paper, a new type of anti-tension equipment is proposed. It consists of two steel frames: one is shape "□", and the other shape "∏", which are perpendicularly connected together. There are diagonal braces and short columns made of rebars on the top of shape "□" steel frame. A small-scale model was first tested, and then a series of parametric study were performed using FEA. In the FEA, the nonlinearity of material and geometry were considered. The yielding and ultimate loads, as well as the stress distribution of the equipment, were investigated for the vertical tensile load condition, considering different shapes of structure, steel materials, and constraint conditions. FEA results match well with the test results. Furthermore, FEA results show that the anti-tension equipment with double column is more effective than that with single column, especially in the case of eccentric tension state. The containment of the bar by the concrete is effective in increasing the ultimate load in the condition of eccentric tension state. Stiffening strips added to the vertical steel arms can significantly increase the ultimate capacity of the equipment. Mostly, as the state of eccentricity increases, the ultimate capacity of the anti-tension equipment decreases.